Labels - Bartmanski, Dominik, 1978- author.
1 online resource (328 pages).
Keywords: The music industry is dominated today by three companies. Outside of it, thousands of small independent record labels have developed despite the fact that digitalization made record sales barely profitable. How can those outsiders not only survive, but thrive within mass music markets? What makes them meaningful, and to whom? Dominik Bartmanski and Ian Woodward show how labels act as taste-makers and scene-markers that not only curate music, but project cultural values which challenge the mainstream capitalist music industry. Focusing mostly on labels that entered independent electronic music after 2000, the authors reconstruct their aesthetics and ethics. The book draws on multiple interviews with labels such as Ostgut Ton in Berlin, Argot in Chicago, 100% Silk in Los Angeles, Ninja Tune in London, and Goma Gringa in Sao Paulo. Written by the authors of Vinyl, this book is essential reading for anyone with an interest in the contemporary recording industry, independent music, material culture, anthropology, sociology, and cultural studies.